Virtual Batch Manufacturing - Benešl, Tomáš (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2018)
This paper describes a possible way to create digital twin of a batch production process. This virtual model of the batch system can be used for testing ISA-88 and ISA-95 with a virtual or real PLC without real system. There is also a possible use for education in labs with PLCs to show a behavior of a batch actors (valve, mixer, heater etc.) and ways to control, which can be tested in the virtual manufacturing system.
Keywords: ISA-95; ISA-88; Siemens; PLC; Step7; C#; Virtual manufacturing; Industry 4.0